Graphene-based electrothermal film, preparation method thereof and application of graphene-based electrothermal film in heating chassis of chef machine
By optimizing the dispersion and treatment process of graphene films, combined with electrochemical polymerization and heat treatment technology, the electric heating performance and hydrophobic oil-resistant properties of graphene-based electric heating films are improved, and the problems of insufficient electric heating performance and poor hydrophobicity in the existing technology are solved, achieving efficient, energy-saving and durable chef heating chassis materials.
Patent Information
- Application Number
- CN202510329807.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing graphene-based electric-thermal films have shortcomings in electric heating performance and hydrophobic oil-resistant properties, and are difficult to meet the needs of modern smart kitchen appliances for high efficiency, energy saving and precise temperature control.
Through the design of graphene oxide dispersion, sonication, vacuum suction filtration and thermochemical reduction, the structural uniformity, conductivity and thermal stability of graphene films are enhanced. The coordinated optimization method of electrochemical polymerization, phased heat treatment and hot press integration is adopted to form a polymer/graphene composite film to improve conductivity, interface stability and structural uniformity. At the same time, through the coordinated optimization design of lithium bistrifluoromethanesulfonimide solution, the electric heating performance and hydrophobic oil stain resistance are enhanced.
The high conductivity, thermal stability and hydrophobic oil-fouling resistance of graphene-based electric heating films have been significantly improved, and the heating efficiency, energy-saving performance, durability and safety of the chef's heating chassis have been improved.
Smart Images

Figure CN119854985A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electric heating materials, and in particular to a graphene-based electric heating film, a preparation method thereof, and an application thereof in a heating chassis of a food processor. Background Art
[0002] In modern kitchen equipment, the chef machine, as a multifunctional cooking device, is widely used in food processing, mixing, heating and other links. Its heating chassis, as a core component, determines the heating efficiency, temperature control accuracy and long-term stability of the equipment. Although traditional metal electric heating elements have high thermal conductivity, they often have problems such as uneven heating, slow response speed and high energy consumption, which makes it difficult to meet the needs of modern smart kitchen appliances for high efficiency, energy saving and precise temperature control. With the development of functional materials, graphene has become one of the important candidates for new electric heating materials due to its excellent electrical conductivity, thermal conductivity and mechanical properties. Especially in the application of the chef machine heating chassis, the ideal electric heating film should have high electrical conductivity to ensure low resistance loss and efficient electric-heat conversion; at the same time, it should have a good Seebeck coefficient to optimize thermoelectric performance and improve temperature control accuracy. In addition, due to the complex working conditions such as high humidity and high temperature fume in the kitchen environment, the electric heating film needs to have good hydrophobic and oil-proof properties to prevent water vapor and oil from attenuating the material performance and improve the service life and safety of the equipment. Therefore, developing a graphene-based electric heating film with high electrothermal conversion efficiency and excellent hydrophobic and oil-proof properties can not only improve the heating efficiency and energy-saving performance of the food processor, but also enhance its durability and safety, further promoting technological progress and market application expansion in the smart kitchen appliance industry.
[0003] At present, graphene-based electric heating films have received extensive attention in the field of electric heating equipment, and have shown excellent electric heat conversion capabilities to a certain extent. However, the prior art still has many shortcomings, especially in terms of optimizing electric heat performance and improving hydrophobic and oil-proof properties. The Chinese patent with publication number CN117246023A discloses a method for preparing a graphene film, a graphene film and an electric heating floor, which achieves a rapid heating effect through the high thermal conductivity of graphene, but due to the lack of an effective interface optimization strategy, the resistivity of the film is high, and the electric-heat conversion efficiency is limited, which affects the overall heating performance and energy consumption control. In addition, although some studies have attempted to improve the thermoelectric properties of graphene films by doping or composite modification, there are still problems such as poor stability and performance attenuation after long-term use. On the other hand, in terms of hydrophobic and oil-proof, existing graphene-based electric heating films generally lack effective surface modification strategies, which makes the film susceptible to contamination after long-term contact with water vapor and oil, reducing the electric heat performance and increasing the cleaning and maintenance costs. For example, the publication number CN108329679A discloses a method for preparing a solvent-free graphene electric heating film, but the method does not have the hydrophobic and oil-proof design, which makes the hydrophobic layer easy to peel off during long-term use, affecting durability. Therefore, there is an urgent need for a preparation method that can improve the electrothermal conversion efficiency of the graphene film while having stable hydrophobic and oil-proof properties, so as to realize an efficient, energy-saving and durable chef machine heating chassis material, and achieve better heating uniformity and service life. Summary of the invention
[0004] (1) Technical issues solved The purpose of the present invention is to provide a method for preparing a graphene-based electric heating film and the application of the preparation method in a heating chassis of a food processor, so as to solve the problem that the current electric heating film has insufficient electric heating performance and hydrophobic and oil-resistant performance.
[0005] (2) Technical solution In order to achieve the above object, the present invention provides the following technical solutions: A method for preparing a graphene-based electric heating film comprises the following steps: S1. dispersing graphene oxide in deionized water, forming a film by ultrasonic treatment and vacuum filtration, and then drying and thermochemically reducing to obtain a layered graphene film; S2. Dissolve aniline and 3,4-ethylenedioxythiophene monomers, continue to add bis(trifluoromethanesulfonyl)imide lithium solution, mix well and adjust pH with sulfuric acid solution to form a copolymer solution; S3. Using the layered graphene film as the working electrode, applying a constant potential in the electrochemical system for interfacial polymerization, and obtaining a composite film after washing and drying; S4. performing a staged heat treatment on the composite film to optimize the performance; S5. Integrate the composite film on the substrate surface by hot pressing, and perform plasma treatment to form a thermoelectric functional layer to obtain a graphene-based electrothermal film.
[0006] Further, the method of step S1 includes: providing a graphene oxide dispersion, dispersing graphene oxide having a sheet diameter of 5 to 20 μm and an oxygen content of 20 to 30% in deionized water at a mass concentration of 0.5 to 1.5 mg / mL, and uniformly stirring for 30 to 60 min at a stirring rate of 500 to 800 rpm to obtain a uniform dispersion, and then subjecting the obtained dispersion to ultrasonic treatment, wherein the power of the ultrasonic treatment is set to 80 to 120 W, the ultrasonic mode adopts a pulse mode, wherein the ultrasonic treatment is performed for 5 s, and the pause is 5s, the ultrasonic time is controlled at 60-90min, the dispersion after ultrasonic treatment is vacuum filtered to achieve oriented arrangement of graphene oxide and form a self-supporting film, the vacuum degree of the vacuum filtration is 0.08-0.1MPa, the pore size of the filter membrane used is 0.22μm, so as to obtain a graphene oxide film with a thickness of 50-100μm, the obtained graphene oxide film is placed in an environment of 80-120°C and dried for 6-12h, and the dried graphene oxide film is placed in a reducing atmosphere for thermochemical reduction, and the reducing atmosphere is H 2 / N 2 The mixed atmosphere has a volume ratio of 10:90. During the reduction process, it is heated to 300-500°C at a heating rate of 5-10°C / min and kept at this temperature for 60-120min. After the treatment, a layered graphene film is obtained.
[0007] The present invention adopts the design of graphene oxide dispersion, ultrasonic treatment, vacuum filtration and thermochemical reduction to enhance the structural uniformity, electrical conductivity and thermal stability of the graphene film. The uniformity is ensured by optimizing the dispersion conditions, pulsed ultrasound avoids the destruction of the layers, vacuum filtration promotes directional arrangement, and the reducing atmosphere and temperature are controlled to remove oxygen functional groups and restore the conjugated structure, thereby improving the conductivity and reducing defects. The layered graphene film finally obtained has excellent electrical properties, thermal stability and mechanical strength, providing a good foundation for subsequent functional treatment and application.
[0008] Further, the method of step S2 includes: providing a comonomer, mixing aniline and 3,4-ethylenedioxythiophene in a mass ratio of (8~9):1, the weight of the mixture is 12.0~20.0g, and adding the resulting mixture to a dichloromethane solvent, the amount of dichloromethane used is 50~100mL, stirring for 30~45min at a stirring rate of 300~500rpm to form a uniform organic phase solution, then slowly adding a 1mol / L concentration of sulfuric acid solution, controlling the addition flow rate to be 1~2mL / min, and the amount added is based on adjusting the pH value of the system to 2.0~3.0 to form a stable water-organic two-phase interface, further adding a lithium bis(trifluoromethanesulfonyl)imide solution to the resulting system, and continuing to stir for 15~30min to ensure that the system is fully and evenly mixed, and finally forming a stable copolymer solution for standby use.
[0009] Further, the concentration of the lithium bis(trifluoromethanesulfonyl)imide solution in step S2 is 40-50wt%, the solvent is a mixed solvent of acetonitrile and dichloromethane, wherein the volume ratio of acetonitrile to dichloromethane is (2.0-4.0):1, the amount of solution added is 1.0-2.0mL, and the droplet rate is set to 1.0-1.5mL / min.
[0010] The present invention adopts the design of lithium bis(trifluoromethanesulfonyl)imide solution mainly to enhance the synergistic optimization performance of electrothermal performance and hydrophobic and oil-resistant performance. A copolymerization monomer system is formed by mixing aniline and 3,4-ethylenedioxythiophene in a specific mass ratio, combined with the doping regulation of lithium bis(trifluoromethanesulfonyl)imide solution, to achieve the synergistic enhancement of the multi-scale functions of the material. In the preparation process of the copolymer solution, the molecular chains of aniline and 3,4-ethylenedioxythiophene form a stable conjugated structure through π-π stacking and charge transfer interaction, and the introduction of lithium bis(trifluoromethanesulfonyl)imide optimizes the carrier concentration and mobility of the copolymer through its strong electron-withdrawing properties. The mixed solvent system of acetonitrile and dichloromethane not only ensures the efficient dissolution of lithium bis(trifluoromethanesulfonyl)imide, but also promotes the uniform distribution of the dopant in the copolymer matrix through the regulation of the two-phase interface. The gradient addition of sulfuric acid solution stabilizes the water-organic two-phase interface by precisely controlling the pH value, avoiding the uneven distribution of components caused by phase separation. In this process, the fluorinated groups of lithium bis(trifluoromethanesulfonyl imide) form a low-energy barrier on the surface of the composite material through surface energy regulation, giving the material hydrophobic and oil-resistant properties, while its sulfonyl imide groups enhance the ordered arrangement of the copolymer segments through intermolecular dipole effects, thereby improving the conductivity and carrier migration efficiency. The high polarity solvent properties of acetonitrile and the hydrophobic properties of dichloromethane work synergistically to optimize the dissolution kinetics of the dopant and form a nanoscale rough surface structure through microphase separation during solvent evaporation, further enhancing the hydrophobic properties. This coordinated design of the solvent composition ratio and the doping process allows lithium bis(trifluoromethanesulfonyl imide to serve as an effective charge dopant to improve the electrothermal conversion efficiency and as a surface modifier to improve the interfacial properties of the material, ultimately achieving dual optimization of electrothermal performance and surface function.
[0011] Further, in step S3, an electrochemical polymerization method is used to perform interfacial polymerization in a three-electrode system, wherein the layered graphene film obtained in step S1 is used as a working electrode, the copolymer solution prepared in step S2 is used as an electrolyte for electrochemical polymerization, a platinum wire is used as a counter electrode, the diameter of the platinum wire is 0.5-1.0 mm, Ag / AgCl is used as a reference electrode, the internal filling solution of the Ag / AgCl reference electrode is 3 mol / L KCl, a constant potential is applied on a CHI660E electrochemical workstation, and the range of the constant potential is 1.2-1.5 V. During the polymerization process, the temperature is controlled at 25-35° C. and the polymerization is carried out under nitrogen protection conditions. The flow rate of the nitrogen is 50-100 mL / min, the polymerization reaction time is set to 4-6 h, and the stirring rate is set to 200-300 rpm to ensure that the interfacial polymerization is carried out uniformly. After the polymerization reaction is completed, the composite film is taken out and washed with an acidic solution and an organic solvent in turn, wherein the acidic solution is 0.1-0.2 mol / L HCl, the organic solvent is ethanol, the washing times are 3 to 5 times, and the amount of washing liquid used each time is 50 to 100 mL to remove unreacted monomers and impurities. Finally, the washed composite film is placed in a vacuum environment at 60 to 80 ° C and dried for 24 to 30 hours to obtain a polymer / graphene composite film.
[0012] Further, the method of step S4 includes: performing staged heat treatment on the composite film obtained in step S3, first, heating to 200~50°C at a heating rate of 2~5°C / min, and keeping at this temperature for 2~4h, then heating to 300~350°C at a heating rate of 5~10°C / min, and keeping at this temperature for 60~120min, after the heat treatment is completed, allowing the composite film to cool naturally to room temperature to obtain an optimized composite film.
[0013] Furthermore, the method of step S5 includes: integrating the composite film on the surface of the substrate by hot pressing, and improving the interface bonding strength by plasma treatment, the hot pressing parameters are set to a temperature of 180~200°C, a pressure of 5~10MPa, and a holding time of 5~10min, and finally forming a graphene-based electric heating film.
[0014] The present invention adopts a design of electrochemical polymerization combined with staged heat treatment and hot pressing integration, which is mainly used to enhance the interface stability, electrical conductivity and structural uniformity of graphene-based electrothermal films. By performing electrochemical polymerization in a three-electrode system, using a layered graphene film as a working electrode and a copolymerization solution as an electrolyte, the copolymer monomers are induced to undergo interfacial polymerization on the surface of the graphene film under constant potential conditions to form a polymer / graphene composite film. The electrochemical polymerization process is carried out under nitrogen protection, and the polymerization uniformity is ensured and the occurrence of side reactions is suppressed by optimizing the temperature, constant potential and stirring rate. At the same time, a stable electrochemical environment is provided by using an Ag / AgCl reference electrode to achieve controllable deposition of the polymer. After the polymerization reaction, unreacted monomers and impurities are removed by multi-step washing with an acidic solution and an organic solvent to ensure the purity and chemical stability of the resulting composite film, and finally vacuum drying is performed to further improve its structural integrity. Subsequently, the microstructure and interfacial bonding of the composite film were optimized by heat treatment in stages. The low-temperature pretreatment stage was used to promote the initial rearrangement of the polymer segments and improve the internal stability of the material. The crystallinity of the material and the continuity of the conductive path were further enhanced at higher temperatures, thereby effectively improving the carrier transfer efficiency. In this process, the reasonable control of the heating rate and the holding time can help reduce the interfacial thermal stress, avoid the generation of structural defects, and improve the uniformity and conductivity of the composite film. Finally, the film was integrated on the substrate surface by hot pressing, and the temperature, pressure and holding time were optimized to ensure the close bonding between the composite film and the substrate. At the same time, plasma treatment was used to further improve the interfacial bonding, enhance the mechanical stability, and improve the electrothermal conversion efficiency. The multi-step optimization design realizes the synergistic effect of polymer and graphene, so that the conductivity, thermal stability and interfacial adhesion performance of the composite film are significantly improved, thereby giving the final graphene-based electrothermal film excellent comprehensive performance.
[0015] The present invention also discloses a graphene-based thermoelectric film, which is prepared by the above method; The graphene of the thermoelectric film has a layered oriented structure, and the layers are arranged along the plane direction of the film; The graphene sheet has a copolymer evenly distributed on the surface and between the layers; The volume fraction of the graphene is 50-70 vol%; The D / G peak intensity ratio of the graphene is between 0.2 and 0.5.
[0016] Furthermore, the graphene-based electric heating film has an in-plane conductivity of 900-1100 S / cm, a Seebeck coefficient of 68-85 μV / K, and a thermal conductivity of 2.0-4.5 W / (m·K); The mass loss of the graphene-based electric heating film in a thermogravimetric analysis test at 300° C. in an air environment is less than 5%; The contact angle between the graphene-based electric heating film and water is 95-120°.
[0017] The present invention also discloses the application of a graphene-based electric heating film, which is used for a heating chassis of a chef machine. The present invention adopts a design of electrochemical polymerization combined with staged heat treatment and hot pressing integration, which is mainly used to enhance the interface stability, electrical conductivity and structural uniformity of the graphene-based electric heating film. By performing electrochemical polymerization in a three-electrode system, using a layered graphene film as a working electrode and a copolymerization solution as an electrolyte, the copolymer monomer is induced to undergo interfacial polymerization on the surface of the graphene film under constant potential conditions to form a polymer / graphene composite film. The electrochemical polymerization process is carried out under nitrogen protection, and the polymerization uniformity is ensured and the occurrence of side reactions is suppressed by optimizing the temperature, constant potential and stirring rate. At the same time, a stable electrochemical environment is provided by using an Ag / AgCl reference electrode to achieve controllable deposition of the polymer. After the polymerization reaction, unreacted monomers and impurities are removed by multi-step washing with an acidic solution and an organic solvent to ensure the purity and chemical stability of the resulting composite film, and finally vacuum drying is performed to further improve its structural integrity. Subsequently, the microstructure and interfacial bonding of the composite film were optimized by heat treatment in stages. The low-temperature pretreatment stage was used to promote the initial rearrangement of the polymer segments and improve the internal stability of the material. The crystallinity of the material and the continuity of the conductive path were further enhanced at higher temperatures, thereby effectively improving the carrier transfer efficiency. In this process, the reasonable control of the heating rate and the holding time can help reduce the interfacial thermal stress, avoid the generation of structural defects, and improve the uniformity and conductivity of the composite film. Finally, the film was integrated on the substrate surface by hot pressing, and the temperature, pressure and holding time were optimized to ensure the close bonding between the composite film and the substrate. At the same time, plasma treatment was used to further improve the interfacial bonding, enhance the mechanical stability, and improve the electrothermal conversion efficiency. The multi-step optimization design realizes the synergistic effect of polymer and graphene, so that the conductivity, thermal stability and interfacial adhesion performance of the composite film are significantly improved, thereby giving the final graphene-based electrothermal film excellent comprehensive performance.
[0018] (3) Beneficial technical effects 1. The present invention achieves significant improvements in the structural uniformity, electrical conductivity and thermal stability of graphene films through the coordinated optimization of graphene oxide dispersion, ultrasonic treatment, vacuum filtration and thermochemical reduction. Compared with the prior art, the present invention improves the uniformity of the sheets and reduces damage by optimizing the dispersion conditions and pulsed ultrasonic strategy, and combines vacuum filtration to form a highly oriented arrangement, effectively reducing interface defects and thereby enhancing the charge transfer capability. By precisely controlling the reducing atmosphere and temperature, the conjugated structure is restored while removing oxygen functional groups, so that the film has both high conductivity and stability, significantly improving its application value in the fields of flexible electronics, thermal management and sensors.
[0019] 2. The present invention significantly improves the conductivity, interface stability and structural uniformity of graphene-based electrothermal films through the synergistic optimization of electrochemical polymerization, staged heat treatment and hot pressing integration. Compared with the prior art, this solution precisely controls the polymerization process through a three-electrode system, combined with optimized temperature and stirring conditions to ensure uniform deposition of polymers on the surface of the graphene film. Staged heat treatment promotes polymer segment rearrangement, improves crystallinity and charge transfer efficiency, while reducing interfacial thermal stress and improving the structural integrity of the film. Finally, hot pressing combined with plasma treatment enhances substrate bonding, allowing the film to exhibit excellent performance and broad application prospects in the fields of flexible electronics, smart heating and sensors.
[0020] 3. The present invention achieves significant improvements in electrothermal performance and hydrophobic and oil-resistant performance through the synergistic optimization design of lithium bis(trifluoromethanesulfonyl)imide solution. Compared with the prior art, the present invention constructs a stable conjugated structure through a copolymerization system of aniline and 3,4-ethylenedioxythiophene, and optimizes the carrier concentration and mobility by utilizing the strong electron-withdrawing effect of lithium bis(trifluoromethanesulfonyl)imide, thereby improving conductivity and thermal stability. The mixed solvent system of acetonitrile and dichloromethane ensures uniform distribution of dopants, and induces nanoscale rough structures through solvent volatilization, thereby enhancing hydrophobic and oil-resistant performance. The gradient addition of sulfuric acid solution stabilizes the water-organic interface, avoids phase separation, and improves material uniformity. Ultimately, this synergistic optimization strategy gives the material excellent electrothermal conversion efficiency, environmental stability, and interfacial bonding strength, giving it broad application prospects in the fields of intelligent heating, flexible electronics, and antifouling coatings.
[0021] 4. The present invention achieves significant improvements in the conductivity, interface stability and structural uniformity of graphene-based electric heating films through the coordinated optimization of electrochemical polymerization, staged heat treatment and hot pressing integration. Compared with the prior art, the present invention optimizes the carrier transmission channel by precisely controlling the polymerization conditions, and uses staged heat treatment to improve the crystallinity and thermal stability of the material, reduce interface defects, and enhance the continuity of the conductive path. Finally, hot pressing and plasma treatment are used to enhance the substrate bonding strength, so that it has efficient and stable electric heat conversion performance in the heating chassis of the chef machine, improves heating uniformity and service life, and meets the needs of high-performance intelligent heating equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The microstructural morphology of the graphene-based electric heating film prepared in Example 1 of the present invention.
[0023] Figure 2 This is the contact angle of a water drop on the graphene-based electric heating film prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0024] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0025] Example 1
[0026] A method for preparing a graphene-based electric heating film comprises the following steps: S1. dispersing graphene oxide in deionized water, subjecting it to ultrasonic treatment, vacuum filtration and film formation, and then drying and thermochemically reducing it to obtain a layered graphene film; providing a graphene oxide dispersion, dispersing graphene oxide with a flake diameter of 5 μm and an oxygen content of 20% in deionized water at a mass concentration of 0.5 mg / mL, and uniformly stirring for 30 minutes at a stirring rate of 500 rpm to obtain a uniform dispersion, and then subjecting the obtained dispersion to ultrasonic treatment, wherein the power of the ultrasonic treatment is set to 80 W, and the ultrasonic mode is adopted The method comprises the following steps: a pulse mode, wherein the ultrasonic treatment is performed for 5 seconds, and the ultrasonic treatment is paused for 5 seconds, and the ultrasonic time is controlled at 60 minutes. The dispersion after ultrasonic treatment is subjected to vacuum filtration to achieve oriented arrangement of graphene oxide and form a self-supporting film. The vacuum degree of the vacuum filtration is 0.08 MPa, and the pore size of the filter membrane used is 0.22 μm. Thus, a graphene oxide film with a thickness of 50 μm is obtained. The obtained graphene oxide film is placed in an environment of 80° C. and dried for 6 hours. The dried graphene oxide film is placed in a reducing atmosphere for thermochemical reduction. The reducing atmosphere is H 2 / N 2 The mixed atmosphere has a volume ratio of 10:90. During the reduction process, it is heated to 300°C at a heating rate of 5°C / min and kept at this temperature for 60 minutes. After the treatment, a layered graphene film is obtained.
[0027] S2. Aniline and 3,4-ethylenedioxythiophene monomers are mixed and dissolved, and a lithium bis(trifluoromethanesulfonyl)imide solution is continuously added. After mixing evenly, the pH is adjusted with a sulfuric acid solution to form a copolymer solution; a copolymer monomer is provided, and aniline and 3,4-ethylenedioxythiophene are mixed at a mass ratio of 8:1. The weight of the mixture is 12.0 g, and the resulting mixture is added to a dichloromethane solvent, wherein the amount of dichloromethane is 50 mL, and the mixture is stirred for 30 min at a stirring rate of 300 rpm to form a uniform organic phase solution. Subsequently, a sulfuric acid solution with a concentration of 1 mol / L is slowly added, and the addition flow rate is controlled to be 1 mL / min. The amount added is based on adjusting the pH value of the system to 2.0 to form a stable water-organic two-phase interface. The lithium bis(trifluoromethanesulfonyl)imide solution is further added dropwise to the resulting system, and the stirring is continued for 15 min to ensure that the system is fully and evenly mixed, and finally a stable copolymer solution is formed for standby use. The concentration of the lithium bis(trifluoromethanesulfonyl)imide solution was 40 wt %, the solvent was a mixed solvent of acetonitrile and dichloromethane, wherein the volume ratio of acetonitrile to dichloromethane was 2.0:1, the amount of solution added was 1.0 mL, and the dropping rate was set to 1.0 mL / min.
[0028] S3. Using the layered graphene film as the working electrode, applying a constant potential in the electrochemical system for interfacial polymerization, and obtaining a composite film after washing and drying; using an electrochemical polymerization method to perform interfacial polymerization in a three-electrode system, wherein the layered graphene film obtained in step S1 is used as the working electrode, the copolymer solution prepared in step S2 is used as the electrolyte for electrochemical polymerization, a platinum wire is used as the counter electrode, the diameter of the platinum wire is 0.5 mm, Ag / AgCl is used as the reference electrode, the internal filling solution of the Ag / AgCl reference electrode is 3 mol / L KCl, a constant potential is applied on a CHI660E electrochemical workstation, the range of the constant potential is 1.2 V, during the polymerization process, the temperature is controlled at 25°C, and the process is carried out under nitrogen protection conditions, the flow rate of the nitrogen is 50 mL / min, the polymerization reaction time is set to 4 h, and the stirring rate is set to 200 rpm to ensure uniform interfacial polymerization, after the polymerization reaction is completed, the composite film is taken out and washed with an acidic solution and an organic solvent in turn, wherein the acidic solution is 0.1 mol / L HCl, the organic solvent is ethanol, the washing times are 3 times, and the amount of washing liquid used each time is 50 mL to remove unreacted monomers and impurities. Finally, the washed composite film is placed in a vacuum environment at 60° C. and dried for 24 hours to obtain a polymer / graphene composite film.
[0029] S4. The composite film is heat treated in stages to optimize the performance. The composite film obtained in step S3 is heat treated in stages. First, it is heated to 200°C at a heating rate of 2°C / min and kept at this temperature for 2 hours. Then, it is heated to 300°C at a heating rate of 5°C / min and kept at this temperature for 60 minutes. After the heat treatment is completed, the composite film is naturally cooled to room temperature to obtain an optimized composite film.
[0030] S5. The composite film is integrated on the substrate surface by hot pressing, and plasma treatment is performed to form a thermoelectric functional layer to obtain a graphene-based electric heating film. The composite film is integrated on the substrate surface by hot pressing, and plasma treatment is performed to improve the interface bonding strength. The hot pressing parameters are set to a temperature of 180°C, a pressure of 5MPa, and a holding time of 5min, and finally a graphene-based electric heating film is formed.
[0031] The graphene of the thermoelectric film of this embodiment has a layered oriented structure, and the layers are arranged along the plane direction of the film; the copolymer is evenly distributed on the surface of the graphene layer and between the layers; the volume fraction of graphene is 50 vol%; and the D / G peak intensity ratio of graphene is 0.2.
[0032] The in-plane electrical conductivity of the graphene-based electric heating film is 900S / cm, the Seebeck coefficient is 84μV / K, and the thermal conductivity is 2.0W / (m·K); the mass loss of the graphene-based electric heating film in a thermogravimetric analysis test at 300°C in an air environment is less than 5%; the contact angle between the graphene-based electric heating film and water is 95°.
[0033] Depend on Figure 1 It can be seen that the graphene-based electric heating film prepared in Example 1 of the present invention exhibits a typical layered structure, indicating that the graphene sheets have good orientation and stacking in the film. This structure is conducive to the effective transmission of carriers and improves the electrical conductivity and thermal conductivity of the film.
[0034] Example 2
[0035] A method for preparing a graphene-based electric heating film comprises the following steps: S1. dispersing graphene oxide in deionized water, subjecting it to ultrasonic treatment, vacuum filtration and film formation, and then drying and thermochemically reducing it to obtain a layered graphene film; providing a graphene oxide dispersion, dispersing graphene oxide with a flake diameter of 10 μm and an oxygen content of 23% in deionized water at a mass concentration of 0.8 mg / mL, and uniformly stirring it for 39 minutes at a stirring rate of 590 rpm to obtain a uniform dispersion, and then subjecting the obtained dispersion to ultrasonic treatment, wherein the power of the ultrasonic treatment is set to 92 W, and the ultrasonic mode is adopted The method comprises the following steps: a pulse mode, wherein the ultrasonic treatment is performed for 5 seconds and then paused for 5 seconds, and the ultrasonic time is controlled at 69 minutes. The dispersion after ultrasonic treatment is subjected to vacuum filtration to achieve oriented arrangement of graphene oxide and form a self-supporting film. The vacuum degree of the vacuum filtration is 0.086 MPa, and the pore size of the filter membrane used is 0.22 μm. Thus, a graphene oxide film with a thickness of 65 μm is obtained. The obtained graphene oxide film is placed at 92° C. and dried for 8 hours. The dried graphene oxide film is placed in a reducing atmosphere for thermochemical reduction. The reducing atmosphere is H 2 / N 2 The mixed atmosphere has a volume ratio of 10:90. During the reduction process, it is heated to 360°C at a heating rate of 6.5°C / min and kept at this temperature for 78 minutes. After the treatment, a layered graphene film is obtained.
[0036] S2. Aniline and 3,4-ethylenedioxythiophene monomers are mixed and dissolved, and a lithium bis(trifluoromethanesulfonyl)imide solution is continuously added. After mixing evenly, the pH is adjusted with a sulfuric acid solution to form a copolymer solution; a copolymer monomer is provided, and aniline and 3,4-ethylenedioxythiophene are mixed at a mass ratio of 8.3:1. The weight of the mixture is 14.4 g. The resulting mixture is added to a dichloromethane solvent, wherein the amount of dichloromethane is 65 mL, and the mixture is stirred for 35 min at a stirring rate of 360 rpm to form a uniform organic phase solution. Subsequently, a sulfuric acid solution with a concentration of 1 mol / L is slowly added, and the addition flow rate is controlled to be 1.3 mL / min. The amount added is based on adjusting the pH value of the system to 2.3 to form a stable water-organic two-phase interface. The lithium bis(trifluoromethanesulfonyl)imide solution is further added dropwise to the resulting system, and the stirring is continued for 20 min to ensure that the system is fully and evenly mixed, and finally a stable copolymer solution is formed for standby use. The concentration of the lithium bis(trifluoromethanesulfonyl)imide solution was 43 wt %, the solvent was a mixed solvent of acetonitrile and dichloromethane, wherein the volume ratio of acetonitrile to dichloromethane was 2.6:1, the amount of solution added was 1.3 mL, and the dropping rate was set to 1.2 mL / min.
[0037] S3. Using the layered graphene film as the working electrode, applying a constant potential in the electrochemical system for interfacial polymerization, and obtaining a composite film after washing and drying; using an electrochemical polymerization method to perform interfacial polymerization in a three-electrode system, wherein the layered graphene film obtained in step S1 is used as the working electrode, the copolymer solution prepared in step S2 is used as the electrolyte for electrochemical polymerization, a platinum wire is used as the counter electrode, the diameter of the platinum wire is 0.65 mm, and Ag / AgCl is used as the reference electrode, and the internal filling solution of the Ag / AgCl reference electrode is 3 mol / L KCl, a constant potential is applied on a CHI660E electrochemical workstation, the range of the constant potential is 1.29V, during the polymerization process, the temperature is controlled at 28°C, and the polymerization is carried out under nitrogen protection conditions, the flow rate of the nitrogen is 65mL / min, the polymerization reaction time is set to 4.6h, and the stirring rate is set to 230rpm to ensure uniform interfacial polymerization. After the polymerization reaction is completed, the composite film is taken out and washed with an acidic solution and an organic solvent in turn, wherein the acidic solution is 0.13mol / L HCl, and the organic solvent is ethanol. The number of washings is 4 times, and the amount of washing liquid used each time is 65mL to remove unreacted monomers and impurities. Finally, the washed composite film is placed in a vacuum environment at 66°C and dried for 26h to obtain a polymer / graphene composite film.
[0038] S4. The composite film is heat treated in stages to optimize the performance; the composite film obtained in step S3 is heat treated in stages, first, heated to 215°C at a heating rate of 2.9°C / min, and kept at this temperature for 2.6 hours, then heated to 315°C at a heating rate of 6.5°C / min, and kept at this temperature for 78 minutes. After the heat treatment is completed, the composite film is naturally cooled to room temperature to obtain an optimized composite film.
[0039] S5. The composite film is integrated on the substrate surface by hot pressing, and plasma treatment is performed to form a thermoelectric functional layer to obtain a graphene-based electric heating film. The composite film is integrated on the substrate surface by hot pressing, and plasma treatment is performed to improve the interface bonding strength. The hot pressing parameters are set to a temperature of 186°C, a pressure of 6.5MPa, and a holding time of 6.5min, and finally a graphene-based electric heating film is formed.
[0040] The graphene of the thermoelectric film of this embodiment has a layered oriented structure, and the layers are arranged along the plane direction of the film; the copolymer is evenly distributed on the surface of the graphene layer and between the layers; the volume fraction of graphene is 56 vol%; and the D / G peak intensity ratio of graphene is 0.29.
[0041] The in-plane conductivity of the graphene-based electric heating film is 960S / cm, the Seebeck coefficient is 79μV / K, and the thermal conductivity is 2.8W / (m·K); the mass loss of the graphene-based electric heating film in a thermogravimetric analysis test at 300°C in an air environment is less than 5%; the contact angle of the graphene-based electric heating film with water is 99°.
[0042] Example 3
[0043] A method for preparing a graphene-based electric heating film comprises the following steps: S1. dispersing graphene oxide in deionized water, subjecting it to ultrasonic treatment, vacuum filtration and film formation, and then drying and thermochemical reduction to obtain a layered graphene film; providing a graphene oxide dispersion, dispersing graphene oxide with a sheet diameter of 14 μm and an oxygen content of 26% in deionized water at a mass concentration of 1.1 mg / mL, and uniformly stirring for 48 minutes at a stirring rate of 680 rpm to obtain a uniform dispersion, and then subjecting the obtained dispersion to ultrasonic treatment, wherein the power of the ultrasonic treatment is set to 104 W, and the ultrasonic mode adopts a pulsed mode. The dispersion after ultrasonic treatment was subjected to vacuum filtration to achieve oriented arrangement of graphene oxide and form a self-supporting film. The vacuum degree of the vacuum filtration was 0.092 MPa, and the pore size of the filter membrane used was 0.22 μm. A graphene oxide film with a thickness of 80 μm was obtained. The obtained graphene oxide film was placed in an environment of 104° C. and dried for 10 h. The dried graphene oxide film was placed in a reducing atmosphere for thermochemical reduction. The reducing atmosphere was H 2 / N 2 The mixed atmosphere has a volume ratio of 10:90. During the reduction process, it is heated to 420°C at a heating rate of 8°C / min and kept at this temperature for 96 minutes. After the treatment, a layered graphene film is obtained.
[0044] S2. Aniline and 3,4-ethylenedioxythiophene monomers are mixed and dissolved, and a lithium bis(trifluoromethanesulfonyl)imide solution is continuously added. After mixing evenly, the pH is adjusted with a sulfuric acid solution to form a copolymer solution; a copolymer monomer is provided, and aniline and 3,4-ethylenedioxythiophene are mixed at a mass ratio of 8.6:1. The weight of the mixture is 16.8 g, and the resulting mixture is added to a dichloromethane solvent, wherein the amount of dichloromethane is 80 mL, and the mixture is stirred for 39 min at a stirring rate of 420 rpm to form a uniform organic phase solution. Subsequently, a sulfuric acid solution with a concentration of 1 mol / L is slowly added, and the addition flow rate is controlled to be 1.6 mL / min. The amount added is based on adjusting the pH value of the system to 2.6 to form a stable water-organic two-phase interface. The lithium bis(trifluoromethanesulfonyl)imide solution is further added dropwise to the resulting system, and the stirring is continued for 24 min to ensure that the system is fully and evenly mixed, and finally a stable copolymer solution is formed for standby use. The concentration of the lithium bis(trifluoromethanesulfonyl)imide solution was 46 wt %, the solvent was a mixed solvent of acetonitrile and dichloromethane, wherein the volume ratio of acetonitrile to dichloromethane was 3.2:1, the amount of solution added was 1.6 mL, and the dropping rate was set to 1.3 mL / min.
[0045] S3. Using the layered graphene film as the working electrode, applying a constant potential in the electrochemical system for interfacial polymerization, and obtaining a composite film after washing and drying; using an electrochemical polymerization method to perform interfacial polymerization in a three-electrode system, wherein the layered graphene film obtained in step S1 is used as the working electrode, the copolymer solution prepared in step S2 is used as the electrolyte for electrochemical polymerization, a platinum wire is used as the counter electrode, the diameter of the platinum wire is 0.8 mm, and Ag / AgCl is used as the reference electrode, and the internal filling solution of the Ag / AgCl reference electrode is 3 mol / L KCl, a constant potential is applied on a CHI660E electrochemical workstation, the range of the constant potential is 1.38V, during the polymerization process, the temperature is controlled at 31°C, and the polymerization is carried out under nitrogen protection conditions, the flow rate of the nitrogen is 80mL / min, the polymerization reaction time is set to 5.2h, and the stirring rate is set to 260rpm to ensure uniform interfacial polymerization. After the polymerization reaction is completed, the composite film is taken out and washed with an acidic solution and an organic solvent in turn, wherein the acidic solution is 0.16mol / L HCl, and the organic solvent is ethanol. The number of washings is 4 times, and the amount of washing liquid used each time is 80mL to remove unreacted monomers and impurities. Finally, the washed composite film is placed in a vacuum environment at 72°C and dried for 28h to obtain a polymer / graphene composite film.
[0046] S4. The composite film is heat treated in stages to optimize the performance. The composite film obtained in step S3 is heat treated in stages. First, it is heated to 230°C at a heating rate of 3.8°C / min and kept at this temperature for 3.2 hours. Then, it is heated to 330°C at a heating rate of 8°C / min and kept at this temperature for 96 minutes. After the heat treatment is completed, the composite film is naturally cooled to room temperature to obtain an optimized composite film.
[0047] S5. The composite film is integrated on the substrate surface by hot pressing, and plasma treatment is performed to form a thermoelectric functional layer to obtain a graphene-based electric heating film. The composite film is integrated on the substrate surface by hot pressing, and plasma treatment is performed to improve the interface bonding strength. The hot pressing parameters are set to a temperature of 192°C, a pressure of 8MPa, and a holding time of 8min, and finally a graphene-based electric heating film is formed.
[0048] The graphene of the thermoelectric film of this embodiment has a layered oriented structure, and the layers are arranged along the plane direction of the film; the copolymer is evenly distributed on the surface of the graphene layer and between the layers; the volume fraction of graphene is 62 vol%; and the D / G peak intensity ratio of graphene is 0.38.
[0049] The in-plane conductivity of the graphene-based electric heating film is 1020S / cm, the Seebeck coefficient is 73μV / K, and the thermal conductivity is 3.5W / (m·K); the mass loss of the graphene-based electric heating film in a thermogravimetric analysis test at 300°C in an air environment is less than 5%; the contact angle of the graphene-based electric heating film with water is 108°.
[0050] Example 4
[0051] A method for preparing a graphene-based electric heating film comprises the following steps: S1. dispersing graphene oxide in deionized water, subjecting it to ultrasonic treatment, vacuum filtration and film formation, and then drying and thermochemically reducing it to obtain a layered graphene film; providing a graphene oxide dispersion, dispersing graphene oxide with a flake diameter of 20 μm and an oxygen content of 30% in deionized water at a mass concentration of 1.5 mg / mL, and uniformly stirring it for 60 minutes at a stirring rate of 800 rpm to obtain a uniform dispersion, and then subjecting the obtained dispersion to ultrasonic treatment, wherein the power of the ultrasonic treatment is set to 120 W, and the ultrasonic mode is adopted The method comprises the following steps: a pulse mode, wherein the ultrasonic treatment is performed for 5 seconds, and the ultrasonic treatment is paused for 5 seconds, and the ultrasonic time is controlled at 90 minutes. The dispersion after ultrasonic treatment is subjected to vacuum filtration to achieve oriented arrangement of graphene oxide and form a self-supporting film. The vacuum degree of the vacuum filtration is 0.1 MPa, and the pore size of the filter membrane used is 0.22 μm. Thus, a graphene oxide film with a thickness of 100 μm is obtained. The obtained graphene oxide film is placed in an environment of 120° C. and dried for 12 hours. The dried graphene oxide film is placed in a reducing atmosphere for thermochemical reduction. The reducing atmosphere is H 2 / N 2 The mixed atmosphere has a volume ratio of 10:90. During the reduction process, it is heated to 500°C at a heating rate of 10°C / min and kept at this temperature for 120 minutes. After the treatment, a layered graphene film is obtained.
[0052] S2. Aniline and 3,4-ethylenedioxythiophene monomers are mixed and dissolved, and a lithium bis(trifluoromethanesulfonyl)imide solution is continuously added. After mixing evenly, the pH is adjusted with a sulfuric acid solution to form a copolymer solution; a copolymer monomer is provided, and aniline and 3,4-ethylenedioxythiophene are mixed at a mass ratio of 9:1. The weight of the mixture is 20.0 g, and the resulting mixture is added to a dichloromethane solvent, wherein the amount of dichloromethane is 100 mL, and the mixture is stirred for 45 min at a stirring rate of 500 rpm to form a uniform organic phase solution. Subsequently, a sulfuric acid solution with a concentration of 1 mol / L is slowly added, and the addition flow rate is controlled to be 2 mL / min. The amount added is based on adjusting the pH value of the system to 3.0 to form a stable water-organic two-phase interface. The lithium bis(trifluoromethanesulfonyl)imide solution is further added dropwise to the resulting system, and stirring is continued for 30 min to ensure that the system is fully and evenly mixed, and finally a stable copolymer solution is formed for standby use. The concentration of the lithium bis(trifluoromethanesulfonyl)imide solution was 50 wt %, the solvent was a mixed solvent of acetonitrile and dichloromethane, wherein the volume ratio of acetonitrile to dichloromethane was 4.0:1, the amount of solution added was 2.0 mL, and the dropping rate was set to 1.5 mL / min.
[0053] S3. Using the layered graphene film as the working electrode, applying a constant potential in the electrochemical system for interfacial polymerization, and obtaining a composite film after washing and drying; using an electrochemical polymerization method to perform interfacial polymerization in a three-electrode system, wherein the layered graphene film obtained in step S1 is used as the working electrode, the copolymer solution prepared in step S2 is used as the electrolyte for electrochemical polymerization, a platinum wire is used as the counter electrode, the diameter of the platinum wire is 1.0 mm, Ag / AgCl is used as the reference electrode, the internal filling solution of the Ag / AgCl reference electrode is 3 mol / L KCl, a constant potential is applied on a CHI660E electrochemical workstation, the range of the constant potential is 1.5 V, during the polymerization process, the temperature is controlled at 35°C, and the process is carried out under nitrogen protection conditions, the flow rate of the nitrogen is 100 mL / min, the polymerization reaction time is set to 6 h, and the stirring rate is set to 300 rpm to ensure uniform interfacial polymerization, after the polymerization reaction is completed, the composite film is taken out and washed with an acidic solution and an organic solvent in turn, wherein the acidic solution is 0.2 mol / L HCl, the organic solvent is ethanol, the washing times are 5 times, and the amount of washing liquid used each time is 100 mL to remove unreacted monomers and impurities. Finally, the washed composite film is placed in a vacuum environment at 80° C. and dried for 30 hours to obtain a polymer / graphene composite film.
[0054] S4. The composite film is heat treated in stages to optimize the performance; the composite film obtained in step S3 is heat treated in stages, first, heated to 250°C at a heating rate of 5°C / min, and kept at this temperature for 4 hours, then heated to 350°C at a heating rate of 10°C / min, and kept at this temperature for 120 minutes. After the heat treatment is completed, the composite film is naturally cooled to room temperature to obtain an optimized composite film.
[0055] S5. The composite film is integrated on the substrate surface by hot pressing, and plasma treatment is performed to form a thermoelectric functional layer to obtain a graphene-based electric heating film. The composite film is integrated on the substrate surface by hot pressing, and plasma treatment is performed to improve the interface bonding strength. The hot pressing parameters are set to a temperature of 200°C, a pressure of 10MPa, and a holding time of 10min, and finally a graphene-based electric heating film is formed.
[0056] The graphene of the thermoelectric film of this embodiment has a layered oriented structure, and the layers are arranged along the plane direction of the film; the copolymer is evenly distributed on the surface of the graphene layer and between the layers; the volume fraction of graphene is 70 vol%; and the D / G peak intensity ratio of graphene is 0.5.
[0057] The in-plane conductivity of the graphene-based electric heating film is 1100S / cm, the Seebeck coefficient is 68μV / K, and the thermal conductivity is 4.5W / (m·K); the mass loss of the graphene-based electric heating film in the thermogravimetric analysis test at 300°C in an air environment is less than 5%; the contact angle of the graphene-based electric heating film with water is 120°.
[0058] Figure 2 The water drop contact angle of the graphene-based electric heating film prepared in Example 4 is 120°, which proves that the film has strong hydrophobicity. The higher contact angle indicates that the graphene surface has been properly reduced, with fewer oxygen functional groups, and a micro-nano structure may have been formed, making it more difficult for water droplets to wet the film surface. In addition, the addition of lithium bis(trifluoromethanesulfonyl imide) is also conducive to improving the hydrophobicity. This result shows that by optimizing the preparation process, the microstructure and surface characteristics of the graphene-based electric heating film can be regulated, thereby improving its comprehensive performance in terms of electrical conductivity, thermal conductivity and waterproofness.
[0059] Comparative Example 1 It is basically the same as Example 1, except that the diameter of the graphene oxide sheet is 2-5 μm, which leads to a decrease in the orientation of the sheet in the film, forming more interface scattering, and reducing the electrical conductivity and thermal conductivity.
[0060] Comparative Example 2 It is basically the same as Example 1, except that the oxygen content of graphene oxide is 35-40%. Too high content of oxygen functional groups affects the thermochemical reduction effect and reduces the conductivity.
[0061] Comparative Example 3 It is basically the same as Example 1, except that the mass concentration of the graphene oxide dispersion is 0.2 mg / mL. The dispersion concentration is too low, resulting in insufficient stacking density of the sheets during the film formation process, affecting the mechanical properties and conductivity of the final film.
[0062] Comparative Example 4 It is basically the same as Example 1, except that the ultrasonic treatment adopts a continuous mode rather than a pulse mode, which causes serious damage to the graphene oxide sheets and the layered structure, and ultimately reduces the conductivity and thermal stability of the film.
[0063] Comparative Example 5 It is basically the same as Example 1, except that the thermochemical reduction temperature is lowered to 200°C, the oxygen functional groups are not completely removed, and the restored conjugated structure is less, resulting in a decrease in the in-plane conductivity of the graphene-based electrothermal film.
[0064] Comparative Example 6 It is basically the same as Example 1, except that the mass ratio of aniline to 3,4-ethylenedioxythiophene in the copolymerization system is adjusted to 5:1, resulting in a reduction in the π-π stacking structure of the copolymer chain segments, affecting the charge mobility and the overall conductivity of the film.
[0065] Comparative Example 7 The method is basically the same as Example 1, except that the concentration of the lithium bis(trifluoromethanesulfonyl)imide solution is reduced to 20 wt %, and the doping concentration is insufficient, resulting in a decrease in the carrier concentration, which affects the electrothermal conversion efficiency and the conductivity of the film.
[0066] Comparative Example 8 The method is basically the same as Example 1, except that the concentration of the lithium bis(trifluoromethanesulfonyl)imide solution is increased to 60 wt %. Excessive doping leads to enhanced carrier scattering, reduced carrier mobility, and decreased Seebeck coefficient, while affecting the uniformity of the film and reducing conductivity.
[0067] Comparative Example 9 It is basically the same as Example 1, except that the rate of adding the lithium bis(trifluoromethanesulfonyl)imide solution is increased to 3 mL / min, resulting in uneven distribution of the dopant in the system and forming a local concentration gradient, which causes large fluctuations in the conductivity and Seebeck coefficient of the film and reduces the overall performance.
[0068] Comparative Example 10 It is basically the same as Example 1, except that the maximum temperature of the staged heat treatment is reduced to 150° C., resulting in insufficient rearrangement of the polymer chain segments and low material crystallinity, which affects the carrier mobility and thermal stability of the film.
[0069] Performance Testing: Conductivity test: The in-plane conductivity of the graphene-based electric heating film is measured using the Four-Point Probe Method. During the test, four probes are evenly arranged on the surface of the sample, a constant current is applied, and the voltage drop is measured to calculate the in-plane conductivity. This experiment can evaluate the effects of doping, heat treatment, and preparation process on the conductive properties of the film.
[0070] Seebeck coefficient test: Using a thermoelectric test system (ZEM-3 thermoelectric tester), a temperature gradient is applied to both ends of the sample and the generated thermoelectric potential is measured to calculate the Seebeck coefficient. This experiment can evaluate the effect of the material's carrier concentration regulation on the thermoelectric conversion performance.
[0071] Thermal conductivity test: The thermal conductivity of graphene-based electric heating film was tested using the Laser Flash Method (ASTM E1461-13). Using the LFA467 thermal conductivity analyzer, the sample surface was heated by a short pulse laser, the temperature change was monitored to calculate the thermal diffusivity, and the thermal conductivity was calculated by combining the density and specific heat. This experiment can evaluate the thermal transfer efficiency and interface optimization effect of the film.
[0072] Thermal stability test: Thermogravimetric analysis (TGA) was performed according to ASTM E1131-20 standard. The film was heated to 800°C at a heating rate of 10°C / min in an air atmosphere, and the change of mass loss with temperature was monitored to evaluate the thermal stability and thermal decomposition characteristics of the film.
[0073] Hydrophobicity test: According to ASTM D7334-08 standard, a video contact angle meter (Dataphysics OCA15) was used to measure the static contact angle of a water drop on the film surface to evaluate the hydrophobicity and surface energy state of the film.
[0074] Medium corrosion resistance test: According to ASTMG31-21 standard, the film was immersed in 0.1MHCl, 0.1MNaOH and 3.5wt%NaCl solution for 168 hours respectively, and the conductivity and mass change before and after were measured to evaluate its acid and alkali resistance and corrosion resistance.
[0075] The properties of the electric heating films of Examples 1 to 4 and Comparative Examples 1 to 10 are summarized in Table 1.
[0076] Table 1 Performance of the electric heating films of Examples 1 to 4 and Comparative Examples 1 to 10
[0077] The performance of graphene-based electrothermal films is affected by a variety of parameters and microstructures, among which the oxygen content of graphene oxide plays a key role in electrical conductivity, thermal stability and hydrophobicity. When the content of oxygen functional groups is high, the electrical conductivity and thermal conductivity of graphene are reduced, while the hydrophilicity of the film is enhanced and the contact angle is reduced. However, when the oxygen content is moderate and removed through a reasonable reduction process, the conjugated structure of graphene is restored, the carrier mobility is improved, the electrical conductivity is enhanced, and the surface tends to be hydrophobic, and the contact angle increases. The orientation and integrity of graphene sheets also significantly affect the electrical conductivity, thermal conductivity and mechanical stability of the film. When the sheet orientation is high, the transmission path of electrons and phonons is more continuous, which helps to improve the electrical conductivity and thermal conductivity. However, if the sheet is severely damaged or disordered, the carrier scattering is enhanced, the electrical conductivity and thermal conductivity are reduced, and the thermal stability and corrosion resistance of the film will also deteriorate. The type and concentration of dopants affect the electrical conductivity and Seebeck coefficient by regulating the carrier concentration and mobility. Appropriate doping can increase the carrier concentration and enhance the conductivity, but excessive doping may lead to increased carrier scattering, decreased conductivity, and negatively affect the thermoelectric performance. In addition, doping uniformity is also crucial to the performance of the film. Uneven doping distribution may lead to local charge accumulation, which will reduce the overall conductivity, thermoelectric conversion efficiency and corrosion resistance of the film. The heat treatment temperature and method directly determine the degree of reduction of graphene and the microstructure of the film. Higher heat treatment temperatures help to remove oxygen functional groups and improve the conductivity and hydrophobicity of graphene, but too low a temperature may lead to incomplete removal of oxygen functional groups, affecting the electron transfer efficiency and reducing the thermal stability of the film. In summary, optimizing the degree of reduction of graphene oxide, controlling the layer structure, adjusting the doping strategy, and optimizing the heat treatment process are the key to improving the comprehensive performance of graphene-based electrothermal films.
[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a graphene-based electric heating film, characterized in that: The following steps are involved: S1. dispersing graphene oxide in deionized water, forming a film by ultrasonic treatment and vacuum filtration, and then drying and thermochemically reducing to obtain a layered graphene film; S2. Aniline and 3,4-ethylenedioxythiophene monomers were mixed and dissolved, and the lithium bis(trifluoromethanesulfonyl)imide solution was added, and the pH was adjusted with sulfuric acid solution after mixing evenly to form a copolymer solution; S3. Using the layered graphene film as the working electrode, applying a constant potential in the electrochemical system for interfacial polymerization, and obtaining a composite film after washing and drying; S4. performing a staged heat treatment on the composite film to optimize the performance; S5. Integrate the composite film on the substrate surface by hot pressing, and perform plasma treatment to form a thermoelectric functional layer to obtain a graphene-based electrothermal film.
2. The method for preparing a graphene-based electric heating film according to claim 1, characterized in that: The method of step S1 comprises: providing a graphene oxide dispersion, dispersing graphene oxide having a sheet diameter of 5 to 20 μm and an oxygen content of 20 to 30% at a mass concentration of 0.5 to 1.5 mg / mL in deionized water, and uniformly stirring for 30 to 60 min at a stirring rate of 500 to 800 rpm to obtain a uniform dispersion, and then ultrasonically treating the obtained dispersion, wherein the power of the ultrasonic treatment is set to 80 to 120 W, and the ultrasonic mode adopts a pulse mode, wherein the ultrasonic treatment is performed for 5 s, the pause is 5 s, and the ultrasonic time is controlled at 60 to 90 min, and the dispersion after ultrasonic treatment is subjected to vacuum filtration to achieve the uniform dispersion of graphene oxide. The graphene oxide film is arranged in a direction and forms a self-supporting film, the vacuum degree of the vacuum filtration is 0.08-0.1MPa, the pore size of the filter membrane used is 0.22μm, so as to obtain a graphene oxide film with a thickness of 50-100μm, the obtained graphene oxide film is placed in an environment of 80-120℃ and dried for 6-12h, the dried graphene oxide film is placed in a reducing atmosphere for thermochemical reduction, the reducing atmosphere is a H2 / N2 mixed atmosphere, and the volume ratio is 10:
90. During the reduction process, it is heated to 300-500℃ at a heating rate of 5-10℃ / min, and kept at this temperature for 60-120min, and a layered graphene film is obtained after the treatment.
3. The method for preparing a graphene-based electric heating film according to claim 1, characterized in that The method of step S2 includes: providing a comonomer, mixing aniline and 3,4-ethylenedioxythiophene in a mass ratio of (8-9):1, the weight of the mixture is 12.0-20.0 g, and adding the resulting mixture to a dichloromethane solvent, the amount of dichloromethane used is 50-100 mL, stirring for 30-45 min at a stirring rate of 300-500 rpm to form a uniform organic phase solution, then slowly adding a 1 mol / L concentration of sulfuric acid solution, controlling the addition flow rate to be 1-2 mL / min, and the amount of addition is based on adjusting the pH value of the system to 2.0-3.0 to form a stable water-organic two-phase interface, further dropping a lithium bis(trifluoromethanesulfonyl)imide solution into the resulting system, and continuing to stir for 15-30 min to ensure that the system is fully and evenly mixed, and finally forming a stable copolymer solution for standby use.
4. The method for preparing a graphene-based electric heating film according to claim 1, characterized in that: The concentration of the lithium bis(trifluoromethanesulfonyl)imide solution in step S2 is 40-50wt%, the solvent is a mixed solvent of acetonitrile and dichloromethane, wherein the volume ratio of acetonitrile to dichloromethane is (2.0-4.0):1, the amount of solution added is 1.0-2.0mL, and the dropping rate is set to 1.0-1.5mL / min.
5. The method for preparing a graphene-based electric heating film according to claim 1, characterized in that: In step S3, an electrochemical polymerization method is used to perform interfacial polymerization in a three-electrode system, wherein the layered graphene film obtained in step S1 is used as a working electrode, the copolymer solution prepared in step S2 is used as an electrolyte for electrochemical polymerization, a platinum wire is used as a counter electrode, the diameter of the platinum wire is 0.5-1.0 mm, Ag / AgCl is used as a reference electrode, the internal filling solution of the Ag / AgCl reference electrode is 3 mol / L KCl, a constant potential is applied on a CHI660E electrochemical workstation, and the range of the constant potential is 1.2-1.5 V. During the polymerization process, the temperature is controlled at 25-35° C. and the polymerization is carried out under nitrogen protection conditions. The flow rate of the nitrogen is 50-100 mL / min, the polymerization reaction time is set to 4-6 h, and the stirring rate is set to 200-300 rpm to ensure that the interfacial polymerization is carried out uniformly. After the polymerization reaction is completed, the composite film is taken out and washed with an acidic solution and an organic solvent in sequence, wherein the acidic solution is 0.1-0.2 mol / L HCl, the organic solvent is ethanol, the washing times are 3 to 5 times, and the amount of washing liquid used each time is 50 to 100 mL to remove unreacted monomers and impurities. Finally, the washed composite film is placed in a vacuum environment at 60 to 80 ° C and dried for 24 to 30 hours to obtain a polymer / graphene composite film.
6. The method for preparing a graphene-based electric heating film according to claim 1, characterized in that: The method of step S4 includes: performing staged heat treatment on the composite film obtained in step S3, first, heating to 200~50°C at a heating rate of 2~5°C / min, and keeping it at this temperature for 2~4h, then heating to 300~350°C at a heating rate of 5~10°C / min, and keeping it at this temperature for 60~120min, after the heat treatment is completed, allowing the composite film to cool naturally to room temperature to obtain an optimized composite film.
7. The method for preparing a graphene-based electric heating film according to claim 1, characterized in that: The method of step S5 includes: integrating the composite film on the surface of the substrate by hot pressing, and improving the interface bonding strength by plasma treatment, the hot pressing parameters are set to a temperature of 180-200°C, a pressure of 5-10MPa, and a holding time of 5-10min, and finally forming a graphene-based electric heating film.
8. A graphene-based electric heating film, characterized in that: The graphene-based electric heating film is prepared by the preparation method according to any one of claims 1 to 7; The graphene of the electric heating film has a layered oriented structure, and the layers are arranged along the plane direction of the film; The graphene sheet has a copolymer evenly distributed on the surface and between the layers; The volume fraction of the graphene is 50-70 vol%; The D / G peak intensity ratio of the graphene is between 0.2 and 0.
5.
9. A graphene-based electric heating film according to claim 8, characterized in that: The graphene-based electric heating film has an in-plane conductivity of 900-1100 S / cm, a Seebeck coefficient of 68-85 μV / K, and a thermal conductivity of 2.0-4.5 W / (m·K); The mass loss of the graphene-based electric heating film in a thermogravimetric analysis test at 300° C. in an air environment is less than 5%; The contact angle between the graphene-based electric heating film and water is 95-120°.
10. Application of a graphene-based electric heating film prepared by the preparation method as described in any one of claims 1 to 7 or a graphene-based electric heating film as described in any one of claims 8 to 9 in a heating base of a food processor.
Citation Information
Patent Citations
Preparation method of non-solvent graphene electrothermal thin film
CN108329679A
Method for preparing grapheme-quantum dot composite film and solar battery structured by using same
CN102176382A
Method for preparing graphene composite film
CN107275114A
Production technology of graphene nanocomposite film
CN107417940A
Preparation method of composite graphene electrothermal film
CN108892134A